Synthesis, Characterizations and Optimization of Magnesium Oxide Scaffold for Bone Healing Applications - Hadi Mohammed, Lamyaa (Al-Nahrain Journal of Science, 2024)
In this work, the structural properties of Magnesium oxide nanoparticles (MgO NPs) are synthesized by a simple chemical technique. X-ray diffraction pattern (XRD) pattern showed the crystalline nature of MgO NPs. The average diameter of MgO NPs calculated by SEM and XRD was around 19 nm. Energy dispersive X-ray spectroscopy (EDS) spectrum and XRD pattern suggested that prepared MgO NPs were highly pure. The viability of cells in a medium containing MgO-AV composite scaffold was nearly equal to that of MgO, AV, and control, with no statistically significant difference (p>0.05). The Runx2-mediated modulation of gene expressions of the bone biomarkers ALP and OCN was investigated to determine the mechanism of scaffold-induced improvement in bone repair. ALP was immunodetected in the injured site of the right femur twenty-one days after the bone defects were created. The implantation of scaffolds into the bone defect region of the left femur, on the other hand, resulted in a noticeable increase in ALP levels. Similarly, OCN was immunodetected in the right femur’s bone defect site. The implantation of scaffolds into the bone defect location of the left femur, on the other hand, resulted in a significant increase in OCN levels. The low-level diode laser therapy (LLLT) promotes the partially bony incorporation of the xeno bony implantation with the recipient femoral bone, and can successfully fill the space, and support the weight after removing the internal fixation methods, with no body rejection. The histopathological finding at the end of the 6th week post-operation in treatment groups the trabecular bone is mature and wide with little cavity. The control group showed immature and thin trabecular bone, with large cavities, and an area of connective tissues not organized. At the end of 12th weeks, post-operation the treatment groups revealed mature trabecular bone surrounding the bony device and lamellar bone formation with partial bony incorporation, the lacuna and haversian canals of the bony device filled with osteocyte and blood vessels, while in control groups the trabecula bone not mature, and many lucana and havesan canal still empty in the bony device.